The Role of a Female Head Assistant at "Al-Walidaturrahmah" Orphanage in Implementing A Just and Civilized Humanity in Samarinda - Suryaningsi; Andi Muhammad (Salasika, 2020)
This article describes and analyzes the role of Al Walidaturrahmah Orphanage in Samarinda in implementing a just and civilized humanity principle. Also, it tries to find out and analyze the forms of coaching and patterns of character development given to the children at AlWalidaturrahmah Orphanage in Samarinda. This research uses qualitative research with a descriptive approach, using primary data, namely the head and the manager of the orphanage. Secondary data sources were obtained through relevant photos and documents of Al-Walidaturrahmah Orphanage. Data collection techniques were done through observation, interviews, and documentation. The data were collected, reduced, and displayed before conclusions were taken. The study found out that the efforts of AlWalidaturrahmah orphanage in implementing the principles to foster children were quite good. Foster children feel treated fairly and well by the parties. The efforts to develop the institutional foundation for AlWalidaturrahmah orphanage are good enough and by the provisions, because it has been carried out well, and the Al-Walidaturrahmah orphanage children carry out appropriate activities to face their future in society later. The pattern of fostering character education at the Al-Walidaturrahmah orphanage can be said to have been carried out well because the AlWalidaturrahmah orphanage children carry out activities by the second precept and have the character to face their future in society.